Analyzing the factors influencing trust in a construction project: evidence from a Sino-German eco-park in China - Wang, Dedong; Li, Kaili; Fang, Shaoze (Journal of Civil Engineering and Management, 2018)
Trust is regarded as a critical feature and a central mechanism in business transactions, especially in the Chinese guanxi network. In this context, the major objective of this research is to explore the key factors influencing trust in different stages of a construction project from the perspectives of owners and consultants involved in a Sino-German eco-park in China. The analytic network process (ANP) was employed to assess which factors are most closely related to trust and to establish four models to meet the objective of this study. According to the ANP results, trust is strongly influenced by factors that are associated with the mutual interests between owners and consultants. In addition, there are certain differences in the priority of the factors influencing initial trust between owners and consultants, but these gaps gradually decrease over time. The weight of guanxi also decreases over time, and the owners’ and consultants’ guanxi transforms from out-group to in-group focused.